High-Stability High-Energy Picosecond Optical Parametric Chirped Pulse Amplifier as a Preamplifier in Nd：Glass Petawatt System for Contrast Enhancement - 黄庭瑞 潘雪 张鹏 王江峰 欧阳小平 李学春 (Chinese physics letters, 2017)
We demonstrate a novel picosecond optical parametric preamplification to generate high-stability, high-energy and high-contrast seed pulses. The 5ps seed pulse is amplified from 60pJ to 300μJ with an 8.6ps/ 3mJ pump laser in a signal stage of short pulse non-collinear optical parametric chirped pulse amplification. The total gain is more than 106 and the rms energy stability is under 1.35%. The contrast ratio is higher than 10s within a scale of 20ps before the main pulse. Consequently, the improvement factor of the signal contrast is approximately equal to the gain 106 outside the pump window.